2004
DOI: 10.1532/ijh97.03091
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Cells and Myocardial Regeneration

Abstract: Hematopoietic stem cell (HSC) plasticity and its clinical application have been studied profoundly in the past few years. Recent investigations indicate that HSC and other bone marrow stem cells can develop into other tissues. Because of the high morbidity and mortality of myocardial infarction and other heart disorders, myocardial regeneration is a good example of the clinical application of HSC plasticity in regenerative medicine. Preclinical studies in animals suggest that the use of this kind of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Our previous studies showed that MSCs can differentiate into epidermal cells and endothelial cells (EC) in vivo under trauma 3 . Because of these characteristics, MSCs have been widely used in cell therapy, 4,5 tissue engineering, 6,7 gene therapy, 8 and immunotherapy 9 …”
mentioning
confidence: 99%
“…Our previous studies showed that MSCs can differentiate into epidermal cells and endothelial cells (EC) in vivo under trauma 3 . Because of these characteristics, MSCs have been widely used in cell therapy, 4,5 tissue engineering, 6,7 gene therapy, 8 and immunotherapy 9 …”
mentioning
confidence: 99%
“…To date, most studies about cardiac repair with stem cells have employed adult stem cells [20-22]. However, experimental and theoretical considerations suggest that ESCs may have advantageous properties for tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…This was thought to be secondary to de novo myocar- dial regeneration. Some studies [15,51] have suggested that these protective effects may be due to release of paracrine protective factors rather than de novo myocardial regeneration. When the cardiomyocytes are subjected to ischemia, they produce tumor necrosis factor [52].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this study further demonstrates that hypoxia also stimulates increased VEGF and HGF production in human MSCs. Some of these growth factors may be protective to the myocardium [12, 15,51]. Pretreatment of rat hearts prior to ischemia reperfusion injury with adult progenitor cells significantly improved the recovery of left ventricular function [14].…”
Section: Discussionmentioning
confidence: 99%